2021
DOI: 10.1101/2021.02.25.432838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Misinformation, Perceptions Towards COVID-19 and Willingness to be Vaccinated: A Population-Based Survey in Yemen

Abstract: Background Since the beginning of the COVID-19 outbreak, many pharmaceutical companies were racing to develop a safe and effective COVID-19 vaccine. Simultaneously, rumors and misinformation about COVID-19 were and still widely spreading. Therefore, this study aimed to investigate the prevalence of COVID-19 misinformation among the Yemeni population and its association with vaccine acceptance and perceptions. Methods A cross-sectional online survey was conducted in four major cities in Yemen. The constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Studies investigating the determinants of COVID-19 vaccine attitudes (see [7,8] for reviews) typically found them to be more negative among low-income [9][10][11], less educated [3,12] populaces, and among ethnic minorities [11,12] and the young [3,11]. Some authors [9][10][11] identify higher COVID-19 vaccine acceptance in males but a major study by Lazarus et al [3] shows the opposite.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies investigating the determinants of COVID-19 vaccine attitudes (see [7,8] for reviews) typically found them to be more negative among low-income [9][10][11], less educated [3,12] populaces, and among ethnic minorities [11,12] and the young [3,11]. Some authors [9][10][11] identify higher COVID-19 vaccine acceptance in males but a major study by Lazarus et al [3] shows the opposite.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies investigating the determinants of COVID-19 vaccine attitudes (see [7,8] for reviews) typically found them to be more negative among low-income [9][10][11], less educated [3,12] populaces, and among ethnic minorities [11,12] and the young [3,11]. Some authors [9][10][11] identify higher COVID-19 vaccine acceptance in males but a major study by Lazarus et al [3] shows the opposite. International comparisons suggest the most positive attitudes are in Asian countries with a high level of trust in the central government and more negative in Central and Eastern Europe [3,4], possibly as a legacy of Soviet communism [13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This study findings show that misinformation exposure of COVID-19 vaccine was not associated with willingness to be vaccinated. A study in Yemen indicated a clear relationship between misinformation and willingness to COVID-19 vaccination 27 . Moreover, another study revealed that misinformation exposure had declined the intention to be vaccinated among people in UK and USA who previously agreed on the COVID-19 vaccine 15 .…”
Section: Discussionmentioning
confidence: 99%